UPAYA MENINGKATKAN MINAT BELAJAR SISWA PADA PELAJARAN BAHASA ARAB DENGAN MENGGUNAKAN METODE PEER TEACHING - Dhayfullah, Fatah Afif; Priyatna, Oking Setia; Hamdani, Ikhwan (JPG: Jurnal Pendidikan Guru, 2022)
Islamic religious education is an effort to foster and nurture students so that they can always understand the teachings of Islam as a whole. Islamic religious education is incomplete if we do not learn a very important subject, namely Arabic. With us learning Arabic lessons we can not only read the Koran but we can also appreciate and read it according to the right way to recite Qur’a. In order for students’ interest in learning to grow and develop properly, a teacher needs a method that increases student interest in learning, especially in Arabic lessons. One of the methods that Arabic teachers need is the Peer Teaching method. This study discusses the Efforts to Increase Students’ Interest in Learning Arabic Using the Peer Teaching Method. The purpose of this study was to find out (1) to increase students’ interest in learning Arabic by using the Peer Teaching method at the Madrasah Aliyah Terpadu (MAT) Darul Fallah Ciampea Campus Dua in the 2019/2020 school year. In this study, the type of Classroom Action Research (CAR) is used with Kemmis and McTaggart’s CAR model approach. Observations were made by planning, implementing, observing, and reflecting on students at MAT Darul Fallah Ciampea Campus Dua. The results of this study indicate that the application of the peer teaching method can increase student participation and interest in learning in learning Arabic. The peer teaching method makes students more active in participating in learning, this is proven by the increase in students asking questions and answering questions.